Real‐world data from a single Greek centre on the use of secukinumab in plaque psoriasis: effectiveness, safety, drug survival, and identification of patients that sustain optimal response. (28th February 2020) - Rompoti, N.; Sidiropoulou, P.; Panagakis, P.; Stratigos, A.; Papoutsaki, M.; Stefanaki, E.; Vavouli, C.; Politou, M.; Befon, A.; Kostakis, P.; Rigopoulos, D.; Nicolaidou, E.
Abstract: Background: Few studies have investigated the long‐term outcomes of secukinumab in real‐life psoriasis treatment where diverse patient profiles require a personalized approach. Objectives: To determine long‐term performance of secukinumab in moderate‐to‐severe plaque psoriasis, and identify potential clinical factors predictive of sustained optimal response under real‐world conditions. Methods: In this 78‐week, single‐centre, retrospective study, effectiveness, safety and drug survival of secukinumab were evaluated. Effectiveness data are reported as observed. Co‐primary endpoints were absolute Psoriasis Area and Severity Index (PASI) ≤3 at week 4, 16, 52, 78, and clinical predictors of PASI ≤3 and PASI100 responses at week 52 and 78. Results: A total of 85 patients (75.3% male; mean age 48.6 years) were included. Absolute PASI ≤3 was achieved in 73% and 83% of patients at week 52 and 78, respectively. PASI 75/90/100 responses at week 52 (71.6%, 50.8%, and 40.3%, respectively) were sustained at week 78 (73.6%, 64.2%, and 45.3%, respectively). Median absolute PASI remained low at week 52/78 (0.9/0.6, respectively), while mean absolute PGA also sustained low (0–1) values after 16–78 weeks. Investigator's Global Assessment 0/1 response rate was maintained by week 52/78 (72/83%, respectively). The drug survival rate of secukinumab at week 78 was 79.1%. Treatment was discontinued in 17.9% of patients after an average of 41.7 weeks, mainly due to loss of effectiveness (10.4%). A total of 27% experienced adverse events, without critical safety concerns. Based on multivariate analysis, advanced body mass index (BMI) and presence of ≥3 comorbidities decreased the chance of achieving PASI ≤3 at week 78 [OR (95% CI) 0.78 (0.64–0.97); P = 0.024, and OR (95% CI) 0.045 (0.002–0.83); P = 0.037, respectively]. Conclusions: Secukinumab showed consistently high effectiveness in this real‐life cohort, with an acceptable safety profile. Over time, persistence of PASI ≤3 response appears to be lower in patients with high BMI or multiple comorbidities.